Maxillofacial fractures among Sudanese children at Khartoum Dental Teaching Hospital - Almahdi, Hatim M. (BMC Res Notes, 2016)
BACKGROUND: Maxillofacial fractures in children are less frequent compared to adults but result in special complications affecting the growth, function and esthetics. AIM: The study aimed at assessing the characteristics and the pattern of facial fractures among children seen at Khartoum Teaching Dental Hospital (KTDH). METHOD: The study included 390 patients presenting with maxillofacial trauma at KTDH during a year period (2010–2011). RESULTS: A total of 390 patients, diagnosed with facial fractures, were seen at KTDH; 14.1 % (55) were children below 16 years of age with the mean age of 10 years (SD ± 3.9). The ratio of males to females was 2.2:1. Most fractures were due to road traffic accidents (RTA) 56.4 %, followed by daily living activities 21.8 % and assault 16.4 %. The most prevalent anatomic sites of fractures were mandible 77 %; combination fractures i.e. more than one site 32.7 % and zygomatic-complex (13.5 %). Concomitant injuries were found in 9.1 %. Almost half of the patients were managed conservatively 49.1 %, closed reduction 34.5 % and surgical open reduction 16.4 %. CONCLUSIONS: The findings of this study indicated that pediatric facial fractures constitute 14.1 % of the total number of facial fractures. RTA was the main cause, which should be considered in legislative and preventive strategies.